Rola nauczyciela edukacji wczesnoszkolnej w kształtowaniu (się) przyrodniczej wiedzy naukowej dziecka - Banaszak, Marek (Wydawnictwo Naukowe UAM, 2017)
The text is about the competences of an early education teacher in developing the student’s natural science knowledge. Selected typologies of the teacher’s competences and a constructivist approach towards the student’s knowledge are presented. Moreover, the text shows that experience is a particularly effective method of improving the child’s skills and knowledge related to nature at an early education level.
The Role of an Early Education Teacher in Developing the Child’s Natural Science Knowledge
Keywords: teacher’s competence; natural science education; constructivism; scientific knowledge; popular knowledge